Heterozygosity level and its relationship with genetic variability mechanisms in beans - Garcia da Silva, Arlindo (2017)
Heterozygosity is an extremely important resource in early breeding programs using autogamous plants becauseit is usually associated with the presence of genetic variability. Induced mutation and artificial hybridization can increasedistinctly the proportion of loci in heterozygosis. This study aimed to compare segregating and mutant populations and relate themechanisms used to generate variability with their respective heterozygosity levels tested. The treatments mutant populations(M2, M3, M4, M5, M6and M7), segregating populations (F4, F5and F6) and lines (BRS Pérola and IPR Uirapuru) were evaluatedby multivariate analysis and compared by orthogonal contrasts. The canonical discriminant analysis revealed which responsevariables contributed to differentiate the treatments assessed. All orthogonal contrasts involving the mutant populations showedsignificant differences, except the contrast between M2vs. M3, M4, M5, M6, M7. The orthogonal contrast between the mutant andsegregating populations denotes a significant variation in the interest in genetic breeding. The traits stem diameter (1.41) andnumber of legumes per plant (2.72) showed the highest canonical weight in this contrast. Conversely, number of grains per plant(-3.58) approached the mutant and segregating populations. No significant difference was observed in the linear comparison ofmeans F5vs. F6. The traits are fixed early in the segregant populations, unlike the mutant populations. Comparatively, inducedmutation provides more loci in heterozygosis than artificial hybridization. Selection pressure should vary according to thevariability creation mechanism used at the beginning of the breeding program.